A first look at SQL server 2005 for developers - Beauchemin, Bob (Addison-Wesley, 2004)
Be the first to master SQL Server 2005's breakthrough database development capabilities Few technologies have been as eagerly anticipated as Microsoft SQL Server 2005 ("Yukon"). Now, three SQL Server insiders deliver the definitive hands-on preview--accurate, comprehensive, and packed with examples. A First Look at SQL Server 2005 for Developers starts where Microsoft's white papers and Web articles leave off, showing working developers how to take full advantage of Yukon's key innovations. It draws on exceptional cooperation from Microsoft's Yukon developers and the authors' hands-on access to Yukon since its earliest alpha releases. You'll find practical explanations of Yukon's new data model, built-in .NET hosting, improved programmability, SQL-99 compliance, and much more. Virtually every key concept is illuminated via sample code tested with Microsoft's public beta. Key coverage includes: *Yukon as .NET runtime host: enhancing security, reliability, and performance *Writing procedures, functions, and triggers in .N ET languages *Leveraging powerful new enhancements to T-SQL *The XML data type and XML query languages *SQL Server 2005 as a Web Services platform *Client-side coding: ADO/ADO.NET enhancements, SQLXML, mapping, ObjectSpaces, and more *Using SQL Server 2005's built-in application server capabilities Already committed to SQL Server 2005? Simply evaluating it? Looking to set yourself apart from other SQL Server developers? Whatever your goal, start right here--today. 0321180593B04152004